Impact of Corporate Governance on Market Price of Share and Stock Return in Nepalese Commercial Banks - Poudel, Dilip; Ghalan, Juliya; Khadka, Kamana; Sah, Kanchan; Shahi, Mohin; Sharma, Nishchal (Nepalese Journal of Finance, 2024)
This study examines the effect of corporate governance attributes on market price of share and stock return in Nepalese commercial banks. The dependent variables are market price of share and stock return. Similarly, the independent variables are company size, board size, board diversity, audit committee, non-performing loans, profitability and leverage. The study is based on secondary data of 15 commercial banks with 105 observations for the period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the market price of share and stock return of Nepalese commercial banks.The study showed that audit committee size has a positive effect on stock return. It means that increase in audit committee size leads to increase in stock return. However, leverage ratio has a negative effect on stock return. It means that increase in leverage ratio leads to decrease in stock return. Similarly, profitability has a positive effect on market price of share and stock return. It means increase in bank profit leads to increase in market price of share and stock return. Similarly, board diversity has a positive effect on market price of share and stock return. It implies that increase in female board directors leads to increase in market price of share and stock return. However, nonperforming loans has a negative effect on market price of share. It implies that increase in nonperforming loans leads to decrease in market price of share. Similarly, board size has a positive effect on market price of share and stock return. It means increase in board size leads to increase in market price of share and stock return.